A taxonomic review of the genus Oesyperus (Coleoptera: Carabidae: Harpalini) - Kataev, Boris M. (Zootaxa, 2006)
Based on the study of the type material, the genus Oesyperus Andrewes, 1923, stat. rest. and three included species are redescribed and a key for determination of the species is provided. A relationship of Oesyperus within the Selenophori group is discussed. The following new synonymies are established: Oesyperus Andrewes, 1923 = Merklia Ito, 2004, syn. n., = Merklophonus Ito, 2005, syn. n.; Oesyperus unctulus Andrewes, 1923 = Merklia pubens Ito, 2004, syn. n.